Epidemiology and antimicrobial resistance of Staphylococcus spp. Isolated from clinical canine cases presented at Onderstepoort Veterinary Hospital - Odoi, Agricola (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.